2019
DOI: 10.11604/pamj.2019.32.10.7508
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to combined Antiretroviral therapy (cART) among people living with HIV/AIDS in a Tertiary Hospital in Ilorin, Nigeria

Abstract: Introduction This study aims to assess the treatment adherence rate among People Living With HIV/AIDS (PLWHA) receiving treatment in a Nigerian tertiary Hospital. Methods This was a cross-sectional study that assessed self-reported treatment adherence among adults aged 18 years and above who were accessing drugs for the treatment of HIV. Systematic random sampling method was used to select 550 participants and data were collected by structured interviewer administered q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 37 publications
3
19
1
Order By: Relevance
“…The prevalence of adherence to ART in this study was 89.0%. This finding was lower than that conducted by [16] in Ilorin where the adherence prevalence was 92.6% as low lack of transportation money, travelling and avoiding being seen were the main factors given for non-adherence among them. However, [17] revealed higher prevalence 97.8% which was more than what this study reported.…”
Section: 'It Doesn't Stop Me From Taking My Drugs and After All I Didcontrasting
confidence: 76%
“…The prevalence of adherence to ART in this study was 89.0%. This finding was lower than that conducted by [16] in Ilorin where the adherence prevalence was 92.6% as low lack of transportation money, travelling and avoiding being seen were the main factors given for non-adherence among them. However, [17] revealed higher prevalence 97.8% which was more than what this study reported.…”
Section: 'It Doesn't Stop Me From Taking My Drugs and After All I Didcontrasting
confidence: 76%
“…While [21] and [22] recorded the highest rate of non-adherence due to adverse drug effects at 66.7% and 76.7% out of 500 and 174 participants respectively. [21] argued that ascertaining the specific side effects experienced by the patients was difficult as the self-report given by these patients may have had some element of bias. In order words, there is a possibility that the patients may have provided a socially acceptable answer due to the sensitivity of the questionnaires thus providing incomplete responses.…”
Section: Resultsmentioning
confidence: 95%
“…Adherence to ART by patients has continued to be suboptimal 2 which might be due to multi- factorial causes. Some of such factors reported in the literature include patient-related factors, inconvenient dosing frequency, pill burden, side effects, patient-health-care provider relationships, lack of money for transportation to the hospital, busy schedule, and forgetting 9 , 21 , 22 . Any factor that influences adherence to regimen should be a concern to health care providers.…”
Section: Introductionmentioning
confidence: 99%